Anthropometric and Physiologic Parameters in Cleft Neonates: A Hospital-Based Study - Swati Verma; Falguni Mehta; SukhDev Mishra; Roshan Noor Mohamed; Harshik Kumar A. Parekh; Ramandeep Kaur Sokhi; Anil Kumar Nagarajappa; Mohammad Khursheed Alam (MDPI AG, 2021)
The oro-facial morphology is greatly affected in neonates with a cleft lip and palate. The initial evaluation of neonate's body and maxillary arch dimensions is important for treatment planning and predicting growth in cleft patients. The objective of this study was comparative evaluation of the anthropometric and physiologic parameters of cleft and non-cleft neonates in a hospital-based set up. This cross sectional study was conducted on 88 cleft and non-cleft neonates (n = 44 in each group) aged between 0 and 30 days after obtaining approval from the institutional ethics committee and positive written informed consent from their parents. Neonates' body weight, body length, head length, head circumference, and maxillary arch dimensions were measured. Maxillary arch dimensions were measured on dental casts with digital sliding calipers. Statistical analyses performed using the independent t-test and one-way ANOVA analysis were followed by Bonferroni correction for post-hoc comparison. The results showed statistically significant differences in birth weight (p < 0.0001), head length (p < 0.01), head circumference (p < 0.007), and maxillary arch dimensions (p < 0.0001) between cleft and non-cleft neonates. These findings suggest that cleft neonates had significant anthropometric and physiologic variations than non-cleft neonates.